Pedagogical Content Knowledge (PCK) pada Mahasiswa Calon Guru Matematika - Annis Deshinta Ayuningtyas; Davi Apriandi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
Pedagogical Content Knowledge (PCK) is one of the basic knowledge that pre -services teachers must-have. PCK explained how the teacher linked material knowledge with knowledge about teaching. By mastering PCK pre-services teachers are expected to carry out effective learning. The purpose of this study is to describe the ability of pre-service mathematics teacher PCK. This type of research is descriptive qualitative. The subjects of this study were two pre-service teachers for the Mathematics Education Department at the Universitas Sarjanawiyata Tamansiswa. The instruments used were observation sheets, questionnaire sheets, linear program test questions, and interview guidelines. The data analysis technique of this study used descriptive qualitative analysis techniques. The results showed that based on indicators of PCK ability, pre-service teachers already knew and understood core competencies, basic competencies, and learning indicators and could make learning objectives, learning materials, reference sources, approaches, strategies, methods, and mathematical learning models. In addition, pre-service teachers can also make assessment plans, both the affective, cognitive, and psychomotor domains as well as the remedial and enrichment programs. Pre-service teachers are quite flexible and confident in teaching even though there are pre-service teachers who speak in small voices and the intonation has not varied. When viewed from the material side, the material provided by pre-service teachers to students is good even though there are still a few shortcomings. In general, pre-service teachers have a good understanding of content and pedagogical knowledge in theory, but implementation in planning and learning in class is still lacking